Catalogue of Palaearctic Sericinae (Coleoptera: Scarabaeidae)—revised and updated fourth edition - Ahrens, Dirk; Bezděk, Aleš (Zootaxa, 2024)
The current fourth edition of the Catalogue of Palaearctic Sericinae (Coleoptera: Scarabaeidae) summarizes new progress in the taxonomy of this group, which is now comprised of 1518 valid species group names in the Palaearctic Region (i.e., species and subspecies names). The following necessary taxonomic changes are proposed: 1) Maladera ustinovi (Gusakov, 2021), new combination, is transferred from Cycloserica Reitter, 1896; 2) due to the primary homonymy with Serica verticalis Lansberge, 1886 (now Lepiserica verticalis), the valid name for Maladera verticalis (Fairmaire, 1888) is Maladera hiekei Frey, 1972; 3) Lasioserica umbrina (Blanchard, 1850), new combination, is a senior synonym of Lasioserica maculata maculata (Brenske, 1894).